Liquid Realization in Rutooro - Bickmore, Lee (My University, 2019)
This paper provides a description and analysis of te distribution of the liquids [r] and [l] in Rutooro (E.12), a Ugandan Bantu language. The allophone that appears is conditioned by the backness of both the preceding and following vowel. Assuming /r/ is underlying, it changes to [l] in contexts when the preceding vowel is back and the following vowel is front. A systematic set of apparent surface counter-examples, leading to phrasal minimal pairs, are argued to be the result of the rule applying twice -- both lexically and post lexically, where a separate post-lexical rule of vowel deletion is responsible for the opacity.
Keywords: Rutooro; Liquid realization; Ugandan Bantu language